Fabrication of melt-spun fibers from irradiation modified biocompatible PLA/PCL blends. (5th January 2022) - Huang, Ying; Brünig, Harald; Boldt, Regine; Müller, Michael Thomas; Wießner, Sven
Graphical abstract: Highlights: Bio-based PLA/PCL melt spun fibers were prepared from electron induced reactive processing (EIReP) toughened PLA/PCL blends. Significantly enhanced melt strength and elasticity was achieved for the EIReP modified blends. EIReP modification improved the fiber surface and finally uniform as-spun fibers were achieved. The EIReP modified fibers with 5 wt% PCL showed 48.7 % increase of fracture strain in comparison with that of its non-irradiated fibers. Abstract: The effect of electron induced reactive processing (EIReP) on the properties of biodegradable polylactide/masticated polycaprolactone (PLA/PCL) blends was firstly investigated without introducing any chemical additives. Subsequently, the melt spinnability of EIReP modified PLA/PCL blends was explored by a piston spinning. Different PCL concentrations (0, 5 and 10 wt%), applied dose (0, 12.5 and 25 kGy) and take up speeds (500 and 2000 m min −1 ) were evaluated in order to investigate their influences on the fiber morphology, thermal and mechanical properties. SEM investigation indicated that the non-irradiated PLA/PCL fibers demonstrated less uniform diameter. However, the EIReP modification leads to a homogenous fiber diameter distribution hence uniform as-spun fibers can be produced. The crystallinity of PLA phase increased concomitantly with increased PCL contents for all fibers, whereas it slightly reduced by increasing dose. In addition, the crystallinity degree of neat PLA raised from 6.19 to 36.05% by increasing take up speed from 500 to 2000 m min −1 . Interestingly, the irradiated PLA/PCL blend fibers with 5 and 10 wt% PCL demonstrated an increased fracture strain of 48.7 and 34.4%, respectively, compared with their non-irradiated fibers. It can be due to the enhanced chain entanglements and interfacial bonding between two phases. However, the irradiated fibers demonstrated similar initial modulus and reduced tenacity compared with the non-irradiated fibers.